1991
DOI: 10.1111/j.1547-5069.1991.tb00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Successful Breastfeeding

Abstract: This study of factors related to success in breastfeeding used achievement motivation and information theories to develop the hypotheses. The sample (N = 150) were married, primigravidas, planning to breastfeed. Breastfeeding for at least six weeks was the criterion for success. Pregnant women's achievement motivation and level of information about breastfeeding were found to be positively related to success in breastfeeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…This may indicate that the knowledge the women gained through the antenatal intervention course was usable for them after having given birth. Previous research has demonstrated how a higher level of knowledge among primiparous women in general associates with a longer duration of breast feeding (Rentschler, 1991;Duckett et al, 1998;Kronborg and Vaeth, 2004). The results suggest that primiparous women should learn about breast feeding during pregnancy and thereby gain usable knowledge that prepares them to cope with breast feeding.…”
Section: Variablementioning
confidence: 56%
“…This may indicate that the knowledge the women gained through the antenatal intervention course was usable for them after having given birth. Previous research has demonstrated how a higher level of knowledge among primiparous women in general associates with a longer duration of breast feeding (Rentschler, 1991;Duckett et al, 1998;Kronborg and Vaeth, 2004). The results suggest that primiparous women should learn about breast feeding during pregnancy and thereby gain usable knowledge that prepares them to cope with breast feeding.…”
Section: Variablementioning
confidence: 56%
“…Two other studies, including only primiparous women (24,25), have also established this association. Richardson (26), on the other hand, could not demonstrate a correlation but he did not include parity in the analysis.…”
Section: Discussionmentioning
confidence: 78%
“…The rate of breastfeeding success in this selected group of women at 4 and 8 weeks after discharge was relatively high at 83% and 71%, respectively, and was similar to that reported by Rentschler. 15 The European literature, however, has often reported lower rates. [25][26][27] After adjusting for demographic variables in this study, the only health system factors that proved to be significant were maternal age, graduate education, and quality of the hospital breastfeeding experience.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] Factors that affect breastfeeding success have been examined extensively, primarily in the nursing literature. 5,[15][16][17] However, the impact of the health care delivery system, both in the hospital and after discharge, on breastfeeding success has been less well documented. Finally, although there have been several studies of hospital-based resource use, total resource use for nonhospital-based services has not been quantified.…”
mentioning
confidence: 99%